Uncovering the Capitalist Footprint: An Examination of the Land-People Nexus in Wayanad through Valli - Kathiresan, Kaviya (2024)
The exploitation of Adivasis, by capitalist forces in Wayanad, Kerala, India is a complex issue that has been ongoing for years. Adivasis in Wayanad have faced bonded slavery, been displaced from their lands, faced loss of resources, and other forms of exploitation, often driven by the interests of organisations seeking to profit from the area’s natural resources. This has resulted in the loss of traditional livelihoods, cultural practices, and community structures for the Adivasis, as well as environmental degradation. This research traces this capitalist exploitation and landlessness among the Adivasis through the lens of the novel Valli, originally published in Malayalam by Sheela Tomy and translated into English by Jayasree Kalathil. The study is based on a close reading and analysis of the text and its depiction of the Adivasi community and the challenges they have faced in the context of capitalist development and resource extraction in the post independent Wayanad.